اسلام اور مغرب کا تہذیبی تصادم (ضربِ کلیم کے تناظر میں) - Hussain Zafar, Dr. Zafar (Tabeer e Nau, 2025)
This paper critically examines the theory of civilizational conflict between Western and Islamic thought in the light of Allama Iqbal’s Zarb-e-Kalim. It contrasts the materialistic and scientific outlook of the West with the spiritual and moral foundations of Islam. The study explores that how Western philosophy—represented by Hegel and Marx’s dialectics, Darwin’s theory of evolution, and the theses of Fukuyama and Huntington—constructs history, and how these stand in opposition to the Islamic conception of a Divinely. According to Iqbal, Western civilization, rooted in materialism and internal contradictions, is heading towards decline, while Islamic civilization offers a holistic framework grounded in spirituality, morality, and human freedom. The analysis suggests that the real axis of civilizational conflict is not power or economics, but the fundamental divergence in the worldview of man and the universe.